Persepsi Masyarakat Mengenai Praktik Pengobatan Dukun Sawan di Kecamatan Sukagumiwang, Kabupaten Indramayu - Layla Nur Fitria; Sulyana Dadan; Shinta Julianti (YASIN, 2026)
Although traditional healing practices have been widely studied, research specifically examining community perceptions of dukun sawan healing practices in Sukagumiwang Subdistrict, Indramayu Regency, remains limited. This study aimed to analyze community perceptions of dukun sawan healing practices in the area. The study employed a qualitative approach with a descriptive design and involved four community members, one midwife, and one community leader selected through purposive sampling. Data were collected through in-depth interviews and observations and subsequently analyzed through data reduction, data presentation, and conclusion drawing. The results showed that community perceptions of dukun sawan healing practices were shaped by knowledge transmitted across generations, experiences of undergoing treatment, the influence of family and the social environment, and beliefs in the benefits experienced after treatment. These findings contribute to the development of sociological studies, particularly the sociology of health, by strengthening the application of George Herbert Mead’s symbolic interactionism theory in explaining the process through which meanings associated with traditional healing practices are constructed through social interaction. This study emphasizes that community acceptance of dukun sawan healing is associated not only with individual experiences but also with the social and cultural constructions that develop within the community. The practical implications of this study indicate the importance of providing healthcare services that consider cultural values and local beliefs. Further research is needed to broaden the investigation of community perceptions of dukun sawan healing practices across different social and cultural contexts.